Comments on "Hybrid decision-making method for assessing interdependency and priority of critical infrastructure". (May 2020) - Chuang, Yen-Ching; Liou, James J.H.; Lo, Huai-Wei
Abstract: In this paper we discuss a paper previously published by Chou and Ongkowijoyo (2019) entitled "A hybrid decision-making method for assessing the interdependence and prioritization of critical infrastructure". In that work the authors developed a fuzzy DANP approach to explore the influential network relationships between critical infrastructures, and their corresponding priorities. However, there are three main problems which need to be clarified: (i) the elements and definition of the critical infrastructures are completely consistent with those described Huang, Liou, and Chuang's (2014) work; (ii) the applied model is also almost the same, except for the addition of the fuzzy concept; and (iii) the rationality of the input data and output results in their paper is not clear. These questions raise doubts about the academic and practical value of Chou and Ongkowijoyo's (2019) paper. Thus, in this study we make a comparison between two models using empirical data from Huang et al. (2014). The results show no significant difference between the two methods.